2014
DOI: 10.2119/molmed.2014.00133
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glycine N-Methyltransferase in the Regulation of T-Cell Responses in Experimental Autoimmune Encephalomyelitis

Abstract: Glycine N-methyltransferase (GNMT) is known for its function as a tumor suppressor gene. Since 100% of female Gnmt-/mice developed hepatocellular carcinoma, we hypothesized that Gnmt-/mice may have defective immune surveillance. In this study, we examined the immune modulation of GNMT in T-cell responses using experimental autoimmune encephalomyelitis (EAE). The results showed that EAE severity was reduced significantly in Gnmt-/mice. Pathological examination of the spinal cords revealed that Gnmt-/mice had si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…13,15,31 Notably, GNMT plays a role in the production of interferon-g, which drives synthesis of the macrophage-specific inflammatory marker neopterin. 18,32 This pteridine has been related to risk of major cardiovascular events in humans 32 and potentiated tHcy-mediated risk of CVD in the same core population as the present study. 4 Neopterin was higher among patients with elevated Vit-A in the present study, and the tHcyassociated risk we observed in our study may reflect pro-inflammatory conditions that contribute to atherosclerosis.…”
Section: Potential Mechanismssupporting
confidence: 67%
See 2 more Smart Citations
“…13,15,31 Notably, GNMT plays a role in the production of interferon-g, which drives synthesis of the macrophage-specific inflammatory marker neopterin. 18,32 This pteridine has been related to risk of major cardiovascular events in humans 32 and potentiated tHcy-mediated risk of CVD in the same core population as the present study. 4 Neopterin was higher among patients with elevated Vit-A in the present study, and the tHcyassociated risk we observed in our study may reflect pro-inflammatory conditions that contribute to atherosclerosis.…”
Section: Potential Mechanismssupporting
confidence: 67%
“…15 GNMT is involved not only in the regulation of intracellular homocysteine concentrations, 16 but also in lipid metabolism 17 and cellular immune activation. 18 Taken together, the association of plasma tHcy with risk of CVD may be modified by Vit-A through several biological mechanisms. However, evidence is limited, predominantly experimental and little is known about this relationship in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maturation of BMDCs was determined by the upregulation of CD11c + and costimulatory molecules expression, the cells were stained with PE-conjugated anti-CD11c antibody, then with FITC-conjugated anti-CD40 or anti-CD86 antibodies (all from BD Biosciences), respectively, as described previously47. To measure percentage of CD4 + IL-17A + T cells, intracellular cytokine staining was performed and the cells were stained with APC-conjugated anti-CD4 antibody, then with PE-conjugated anti-IL-17 antibody (BD Biosciences) as described previously53. Cells were analyzed by a FACSCalibur (BD Biosciences) as described previously20.…”
Section: Methodsmentioning
confidence: 99%
“…Glycine N-methyltransferase (GNMT) encodes a tumour suppressor gene recently associated with T cell immune response. In a mouse model of autoimmune encephalomyelitis, the knock down of GNMT reduced the severity of the disease [43]. CUB and sushi multiple domains 1 (CSMD1) is a complement control-related gene that inhibits the activation of complement C3 and has a possible role in lupus erythematosus and schizophrenia [44].…”
Section: Discussionmentioning
confidence: 99%